2019
DOI: 10.1016/j.matt.2019.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Separation and Quantum Tunneling of Photo-generated Carriers Using a Tribo-Induced Field

Abstract: Boosting the photovoltaic power output is the key to large-scale implementation of solar cell technologies for renewable energy applications. Traditional solar energy harvesting is limited by the costly fabrication of p-n junctions, the duration of sunlight irradiation, and theoretical output limit. In this work, Liu et al. demonstrate that the photovoltaic power output can be dramatically enhanced by mechanical friction between a metal and a semiconductor, leading to the development of a new power generation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 38 publications
3
60
0
Order By: Relevance
“…In addition, Zhang and Yang developed the feasibility of InP bulks for a thermo-photovoltaic NG [ 16 ]. Very recently, Liu et al demonstrated Si wafers as suitable tribophotovoltaic materials [ 41 ].…”
Section: Fundamentalsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Zhang and Yang developed the feasibility of InP bulks for a thermo-photovoltaic NG [ 16 ]. Very recently, Liu et al demonstrated Si wafers as suitable tribophotovoltaic materials [ 41 ].…”
Section: Fundamentalsmentioning
confidence: 99%
“…In recent years, direct-current TENGs have attracted intense interest since it provides a novel direction for coscavenging of light and mechanical energies. Liu et al fabricated a tribo-photovoltaic NG with stainless steel/Si/Al configuration [ 41 ]. When friction and irradiation are simultaneously applied, tribo-tunneling current is created and flows towards the Al side.…”
Section: Device Designmentioning
confidence: 99%
See 1 more Smart Citation
“…However, conventional TENGs usually use organic polymer insulation materials, and the charges generated by friction tends to accumulate on the surface of the material, resulting in an alternating output . Recently, semiconductor materials began to attract researchers' interest, and a series of work has made great progress: the tribotunneling nanogenerator based on sliding metal–insulator–semiconductor (MIS) structure, the moving Schottky diode based on metal–semiconductor (MS) structure, the triboelectric cell based on PN junction structure, and other moving heterojunction nanogenerator . Thundat and Liu et al realized an ultrahigh current density MIS nanogenerator due to quantum mechanical tunneling of the ultrathin natural oxide layer .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have designed the creative systematic design of dynamic Schottky diodes, in which the sliding of metals over semiconductors can produce a direct-current electricity output [19][20][21]. Some similar phenomena based on semiconductors have also been dedicated to converting mechanical energy into electricity, which they attribute to the triboelectricity effect [22][23][24][25][26]. In particular, we have proposed the physical picture of the dynamic Schottky diode based on the rebounding effect under the ultrahigh built-in electric field at the interface, which can break the balance between the drift current and diffusion current and generate an electrical output [19,20].…”
Section: Introductionmentioning
confidence: 99%